Characteristics and evaluation of heavy metal pollution in a soil–wheat system of an arid oasis city in northwest China - Shenghui Xu; Changhao Li; Yan Wang; Ao Wu; Guowen Gao; Fei Zang (Ecotoxicology and Environmental Safety, 2024)
In this paper, the Cu and Ni accumulation and contamination levels in agricultural soils and wheat around a smelter in Jinchang City in northwest China were investigated with a combination of field investigations and indoor analytical tests, using a soil–wheat system as the study area. The average Cu and Ni contents in the soil were 119.50 mg kg–1 and 123.40 mg kg–1, respectively, both of which exceeded the local soil background values. The Cu and Ni contents in 46.15% o and 26.92% of sampling sites, respectively, exceeded the screening values for soil contamination risk in agricultural land in China. The average Cu content in different parts of wheat was in the order of roots (24.22 mg kg–1) > leaves (20.11 mg kg–1) > husks (5.51 mg kg–1) > grains (4.05 mg kg–1) > stalks (3.74 mg kg–1). Furthermore, the average Ni content ranked as leaves (24.64 mg kg–1) > roots (21.12 mg kg–1) > husks (6.95 mg kg–1) > stalks (1.75 mg kg–1) > grains (0.38 mg kg–1). The health risk evaluation showed that with average hazard index values of 0.88 for adults and 1.04 for children for Cu and Ni in wheat grain, wheat in this region is unlikely to pose a health risk to adults but may pose a lesser health risk to children. The Ni bio–concentration and translocation factors in the husk and leaves of wheat were greater than those of Cu and smaller than those of Cu in the other parts of wheat. The results of this study provide basic data for the remediation of heavy metal contamination in local agricultural soils.